2005
DOI: 10.1108/15365430580001324
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Employability on Worker Performance

Abstract: In this paper, we show that workers’ performance in firms is conditioned by a set of informational factors and expectations about the future. We also demonstrate that any corporate action that successfully raises workers’ employment expectations will translate into performance gains. In the current uncertain context, firms can raise productivity by offering higher‐value jobs that provide workers with greater opportunities to improve their employability. In this sense, high‐performance work organizations can pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…There is also very limited research on the effects of employability on what is a much more analyzed construct, individual task performance. These scarce empirical works suggest that employees with higher employability are more capable of doing their tasks and are more motivated to make an extra effort, so they will receive a better performance appraisal (Arocena et al, 2007;Villanueva, 2005).…”
Section: Employability and Ethical Behaviormentioning
confidence: 99%
“…There is also very limited research on the effects of employability on what is a much more analyzed construct, individual task performance. These scarce empirical works suggest that employees with higher employability are more capable of doing their tasks and are more motivated to make an extra effort, so they will receive a better performance appraisal (Arocena et al, 2007;Villanueva, 2005).…”
Section: Employability and Ethical Behaviormentioning
confidence: 99%
“…Research is also limited on the effect of employability on a much more analysed construct, individual task performance. The scarce empirical works that do exist suggest that employees with higher employability are more capable of doing their tasks and are more motivated to make an extra effort, so they will get a better task performance appraisal (Villanueva, 2005; Arocena et al ., 2007).…”
Section: Employability and Contingent Rewardmentioning
confidence: 99%
“…In other words, we hypothesize that optimal performance at work requires that an individual employee possesses the occupational knowledge and skills (i.e., competences or career potential; employability) that are necessary to meet their organizational demands, and that these competences can be enhanced by investing in networking activities. Arocena et al (2007) -based on their work in small-and medium-sized enterprises -already concluded that workers' employability is positively associated with their capability of doing their tasks and with their motivation to make extra efforts, herewith resulting in a better task performance appraisal (see also Villanueva, 2005;Hahn and Kim, 2018). However, as scholarly research on the relationship between employability and individual task performance is scarce (Camps and Rodríguez, 2011;Hahn and Kim, 2018), the first contribution of this empirical work is to increase our knowledge on how to safeguard employees' added value and their chances to survive in current labor markets.…”
Section: The Importance Of Intra-organizational Networkingmentioning
confidence: 99%